Numerical modeling of reinforced concrete beams repaired and strengthened with SFRC - Ruano Sandoval, Gonzalo Javier (2015)
Improved tensile properties of steel fiber reinforced concrete (SFRC) make it suitable for repairing and strengthening of reinforced concrete elements. The use of this material as repairing or strengthening material has increased during the last years motivating the development of numerical tools for the design of this type of intervention technique. The numerical simulation of the mechanical behavior of a series of reinforced concrete beams which includes strengthened and repaired beams with high performance self compacting SFRC tested under shear is presented in this paper. SFRC is considered as a composite material composed of concrete matrix and fibers and a simple homogenization approach based on modified mixture theory is used to model its mechanical behavior. An evolutionary algorithm is proposed in order to simulate the whole process of testing, repairing and retesting the beams. The numerical simulations can accurately reproduce flexure characterization tests and predict the bearing capacity of the repaired and strengthened beams tested under shear. Furthermore, other repairing/strengthening options are numerically studied. The numerical results could be useful to improve the design of this kind of intervention techniques.